Evaluation of the Quality of the Housing Environment Using Multi-Criteria Analysis That Includes Energy Efficiency: A Review - Mazur, Łukasz; Bać, Anna; Vaverková, Magdalena Daria; Winkler, Jan; Nowysz, Aleksandra; Koda, Eugeniusz (MDPI AG (Multidisciplinary Digital Publishing Institute-MDPI), 2022)
The quality of the housing environment (HE) is an important issue that has a direct impact on the life of inhabitants. Aiming for quality in residential architecture begins with a well-designed HE, with the designing process being a value that is difficult to evaluate. Nowadays, a well-designed HE takes into account the energy efficiency of a building. An appropriate degree of thermal comfort, which is required by inhabitants, needs to be considered at the design stage. Designers can use building certification programs and multi-criteria analysis to motivate investors to construct buildings in accordance with energy efficiency requirements. These systems respond to the needs of energy efficiency, thermal comfort, sustainable heating, and ventilation. Defining ways and methods to evaluate quality in architectural projects will allow the value of the HE to be improved. For this purpose, a multi-criteria analysis of five systems that can be used to evaluate HE quality and energy efficiency in a temperate climate was conducted: (1) Building For Life 12, (2) Home Quality Mark, (3) Housing Quality Indicators, (4) Système D'évaluation De Logements (Sel), and (5) NF Habitat-NF Habitat HQE. This analysis concerned information about the systems, their applicability in practice, and the applied assessment measures. The article shows that the quality of the HE consists of specific factors that can be distinguished and indicated by evaluation systems. As a result of the carried out assessment of the housing environment, 13 original categories of building assessment criteria were defined. The results of the conducted analysis indicated that it is possible to: (i) identify factors for the improvement of HE quality; (ii) prepare objective systems for the measurement of the HE; and (iii) use such systems in practice, e.g., in the design industry, real estates, and public administration. Moreover, the systems can be used in legal regulations for updating urban policies.
Keywords: building design quality; energy efficiency; certification of buildings; residential buildings; thermal comfort